ANALISIS VARIANS SATU ARAH (ANOVA) UNTUK MEMBANDINGKAN METODE PEMBELAJARAN DI SEKOLAH DASAR - Wahidah Azzahra; Umi Nurzanna; Yuli Pratiwi; Putriyani Damanik; Nanda Wafa Nabila; Adinda Rahmawati; Nurhaswinda, Nurhaswinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study employed a literature review methodology to compare student learning outcomes across learning approaches using one-way analysis of variance (ANOVA). The research methodology employed desk research, which involved reading relevant scientific books and journal articles. Data were collected from secondary sources selected based on their reliability and relevance, and then content analysis methods were applied. The study findings indicate that one-way analysis of variance (ANOVA) is frequently used in educational research to test how well different teaching strategies impact student learning outcomes. Many studies have found significant variations in learning outcomes between the compared learning approaches, including project-based learning, digital learning, and traditional methods. However, some studies have shown no significant differences between learning approaches. The learning environment, student characteristics, and implementation strategies for learning methods all impacted the variation in these findings. The learning environment, student characteristics, and implementation strategies for learning methods all impacted the variation in these findings. One-way analysis of variance (ANOVA) is a relevant and useful statistical methodology in educational research for assessing variations in student learning outcomes based on learning methods. It is hoped that educators and academics will use this research as a reference when selecting effective teaching strategies and creating new educational research.